Ketergantungan Tiga Jenis Tanaman Kehutanan terhadap Mikoriza pada Media Tanah Bekas Tambang Pasir Silika - Putri Aurum; Sri Wilarso Budi; Prijanto Pamoengkas (Jurnal Ilmu Pertanian Indonesia, 2020)
One effort to support the success of reclamation and rehabilitation of ex-silica sand mines is to improve the quality of seedling planted with mycorrhizal inoculation. Each plant has a mycorrhizal dependency which varies depending on the plant species and the level of soil fertility. This study aimed to analyze the mycorrhizal dependency of Kadam (Anthocephalus cadamba), Red Sengon (Albizia chinensis), and Kaliandra (Calliandra calothyrsus) grown on soil growing media from post silica sand mining and amended with compost and lime. The study used completely randomized design with a split plot design consist of two factors, first factor was mycorrhizal inoculation in the form of MycoSilvi inoculum, consisting of two levels and the second factor was soil ameliorant in the form of lime and compost consisting of six levels, each treatment was repeated five times. The results showed that the treatment of lime and MycoSilvi addition showed the highest percentage of mycorrhizal dependency on Kadam, Red Sengon and Kaliandra seedlings, which were 76, 62, and 59% respectively. The addition of lime and compost decreased the degree of relative mycorrhizal dependency of three plants species tested, in line with increasing available P in soil growth medium. Keywords: mycorrhizal dependency, MycoSilvi, post mined soil, soil ameliorant